Responses to Covid-19 threats: An evolutionary psychological analysis - COLARELLI, Stephen M. (Institutional Knowledge at Singapore Management University, 2022)
Responses to Covid-19 public health interventions have been marginally effective. For example, only 64% of the US population has received at least two vaccinations. Because most public health interventions require people to behave in ways that are evolutionarily novel and are mismatched with evolved human perceptual and decision-making mechanisms, it is imperative that we gain a better understanding of how people respond to public health information—including how they respond under different pandemic conditions and how specific groups may differ in their responses. We conducted two studies using data from primarily public sources. We found that state-level Covid-19 threats (e.g., infection and mortality rates) had no relationships with mental health symptoms, suggesting that people were not attending to threat information. This result is consistent with the evolutionary psychological explanation that Covid-19 threat information is insufficient to activate people’s behavioral immune system. Furthermore, individual differences affected how people responded to Covid-19 threats, supporting a niche picking explanation. Finally, aggregate state IQ levels correlated positively with aggregate vaccination rates, suggesting that intelligence can partially counteract the evolutionary novelty of abstract threat information, supporting the savanna-IQ interaction hypothesis. We conclude with policy implications for improving interventions and promoting greater compliance.